Synthesis of Eu-modified luminescent Titania nanotube arrays and effect of voltage on morphological, structural and spectroscopic properties. (July 2020) - Su, Baoze; Wang, Shichao; Yang, Wenbin; Wang, Yao; Huang, Linjun; Popat, Ketul C.; Kipper, Matt J.; Belfiore, Laurence A.; Tang, Jianguo
Abstract: In this work, two type of europium (Eu) modified Titania nanotube arrays (TiO2 -NTs) are demonstrated. Highly ordered TiO2 -NTs were prepared by anodizing the surface of titanium surface at different voltages (30V, 45V, 55V). Eu-doping of TiO2 -NTs was carried out by adding Eu 3+ to the electrolyte during anodization, and Eu-coated TiO2 -NTs were obtained by incubating nanotubes in EuCl3 solution. The surface were characterized by field emission scanning electron microscopy (FESEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectra (XPS), Raman spectroscopy, UV/VIS-NIR spectroscopy and by measuring photoluminescence (PL) spectra. The nanotube diameter decreases as the anodization voltage is decreased, while the wall thickness increases. More importantly, the morphology of the TiO2 -NTs is not influenced by Eu-doping and Eu-coating, except that the nanotube diameter become about 8 nm smaller after Eu-doping. Eu-doped TiO2 -NTs obtained at 55V have the maximum diameter, the highest Eu-doping content, the best stability, the widest band gap and relatively strong photoluminescence. Thus, there is a potential to use these nanotube surfaces for photocatalytic and biosensor applications. Highlights: Europium modified TiO2 nanotube arrays (Europium doped and coated) can be synthesized to have different diameters. Europium doped TiO2 nanotube arrays show a good stability in air and water. Europium doped TiO2 nanotube arrays obtained at 55V shows the best photoluminescence property.